Environmental Knowledge and Politics in Sarawak - Mohd Rizal, Yaakop; Ahmad Redzuan, Mohamad; Mohd Azmi, Mohd Razif; Ing, Nurdin; Ahmad Ali, Seman; Sharifah Aluya, Ali; Sharifah Sabrina, Ali (Human Resource Management Academic Research Society (www.hrmars.com), 2020)
The objective of this study is to examine environmental knowledge and awareness amongst the students of Higher education in Malaysia and to understand their views on environmental security issues. The main method of collecting data is by Questionnaires that involved 948 respondents randomly selected. The data was then analyzed using Statistical Package for Social Sciences (SPSS). The results show that the respondent are well informed, knowledgeable and aware of environmental security issues as the pattern is fairly consistent by sex, age, and ethnic grouping. Findings from this study provide insight into the importance of awareness in generating environmental consciousness and public response towards policy and practices related to the environment. Furthermore, the study captures what it means by environmental security for the respondents. It is important for future analyses to look into this question and to enhance more study related to understanding of environmental security. Keywords: Environmental Knowledge-Awareness –Environmental Security.